Integrasi Accera pare Bagi Kehidupan Masyarakat Parigi Dalam Membangun Solidaritas Peserta Didik - Tahirah, Inas; Astina, I Komang; Wirahayu, Yuswanti Ariani; Susilo, Singgih; Suharto, Yusuf (Universitas Negeri Malang, 2025)
Abstract : Accera pare is a harvest party of the Parigi Village community which is held as a form of gratitude of the farmers for the gifts given by God for being given a smooth harvest. The purpose of this research is to explore the meaning of the accera pare ceremony for the people of Parigi Village and the integration of accera pare in building students' sense of solidarity. The research method used descriptive qualitative with ethnographic approach where the data were analyzed by domain analysis, taxonomy, components and cultural themes. Data sources were obtained through participant observation and in-depth interviews. The results showed that the meaning of the accera pare ceremony for the people of Parigi Village is as a form of respect for ancestors including forms of communication, protection and guardians of nature, as a thanksgiving including prayer, thanksgiving, as a cultural heritage which includes heirlooms, traditional performances and traditional clothes and as a form of human relationship with humans which is realized through deliberation and socialization between communities. The integration of accera pare in building students' solidarity is reflected in kinship, gratitude, mutual cooperation, togetherness and the spirit of sharing. Abstrak : Accera pare merupakan pesta panen masyarakat Desa Parigi yang dilaksanakan sebagai bentuk syukur para petani atas karunia yang diberikan oleh Tuhan karena diberi kelancaran panen. Tujuan penelitian ini untuk menggali makna upacara accera pare bagi masyarakat Desa Parigi dan integrasi accera pare dalam mebangun rasa solidaritas peserta didik. Metode penelitian menggunakan deskriptif kualitatif dengan pendekatan etnografi dimana data dianalisis dengan analisis domain, taksonomi, komponen dan tema budaya. Sumber data diperoleh melalui observasi partisipasi dan wawancara mendalam. Hasil penelitian menunjukkan bahwa makna upacara accera pare bagi masyarakat Desa Parigi adalah sebagai wujud penghormatan kepada leluhur meliputi bentuk komunikasi, perlindungan dan penjaga alam, sebagai ucapan syukur meliputi berdoa, ucapan terima kasih, sebagai warisan budaya yang meliputi peninggalan pusaka, pertunjukkan tradisional dan baju adat dan sebagai bentuk hubungan manusia dengan manusia yang terwujud melalui musyawarah dan sosialisasi antar masyarakat. Integrasi accera pare dalam membangun solidaritas peserta didik tercermin dalam kekeluargaan, rasa syukur, gotong royong, kebersamaan dan semangat berbagi.